Issues of interlingual enantiosemy in Slavic languages (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2013)
The article analyses the issues of interlingual  enantiosemy in contrastive linguistics. It deals with the classification of interlanguage correlations of  some enantiosemic nature. The most frequent enantionyms in Slavic languages are defined. The interdisciplinary aspect of the research is described.
Keywords: contrastive linguistics; homonymy; polysemy; antonymy; enantiosemy